2022
DOI: 10.1021/acsanm.2c00663
|View full text |Cite
|
Sign up to set email alerts
|

Memristor Arrays Formed by Reversible Formation and Breakdown of Nanoscale Silica Layers on Si–H Surfaces

Abstract: Nonvolatile resistive switching, also known as the memristor effect, has emerged as an important concept in the development of neuromorphic computing. Memristive operation shares similarities to the mechanism of biological synapses, making it a promising technology for future artificial intelligence. To date, most memristor platforms are based on the resistive switching of an insulating material separating two metals. For future electrical circuitry that resembles those of synapses and neurons, memristors are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Peiris et al grew silicon oxide hillocks on Si surfaces by C-AFM tip-induced oxidation to fabricate a silica based memristor. 81 The thickness of oxide film was controlled by the magnitude of the applied bias, duration polarity and the Si doping type, i.e., n-type and p-type. Fig.…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%
“…Peiris et al grew silicon oxide hillocks on Si surfaces by C-AFM tip-induced oxidation to fabricate a silica based memristor. 81 The thickness of oxide film was controlled by the magnitude of the applied bias, duration polarity and the Si doping type, i.e., n-type and p-type. Fig.…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%
“…Topography images were then recorded at low bias voltages to check what the effect of the previous bias− voltage applied was (Figure 5a−e). On Si−H surfaces, 48 it was previously demonstrated that the oxide thickness increased with the magnitude of the bias-voltage applied from (1.0 ± 0.36) to (6.3 ± 0.37) nm as the bias-voltage increased from +0.5 to +5 V. Also on Si−H, the oxide square created in the center of the surface becomes clearly visible at +0.5 V. In contrast, on Si−D surfaces, the oxide square does not reach detectable thickness until +5 V. In addition, I−V measurements were performed on and outside the oxide areas. When the bias-voltage applied exceeded +0.5 V, the resulting oxide growth affected the magnitude of the current compared to that recorded on unbiased surfaces (Figure 5k−o).…”
Section: Electrochemical Studiesmentioning
confidence: 99%
“…A possible explanation for negative potential oxidation is that the current-induced dissociation of the Si−H bonds creates radicals which then react with molecular oxygen that initiates oxidation. 48 This oxidation has a detrimental effect on Si devices. For example, oxidation can desorb the monolayer, thereby changing the conductivity and the rate of electron transfer at the interface�a typical measurement used for sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…This significantly extends the probe’s lifetime and may promote more reliable results since the probability of altering probe conditions throughout the measurement is reduced. Also, as current-related damage to the sample’s surface is diminished, this approach may enable the exploration of many other phenomena, including the characterization of delicate samples (like polymer blends for charge transport in organic solar cells), , measure self-accelerated current phenomena (like dielectric breakdown and resistive switching), , probing the influence of local defects in heterostructures (AlGaN/GaN, 3C-SiC layers) , and two-dimensional materials (MoS 2 ), , and even provide better control of oxide growth during nanolithography …”
Section: Introductionmentioning
confidence: 99%